Ultrafast Click Chemistry with Fluorosydnones. (25th August 2016) - Liu, Hui; Audisio, Davide; Plougastel, Lucie; Decuypere, Elodie; Buisson, David‐Alexandre; Koniev, Oleksandr; Kolodych, Sergii; Wagner, Alain; Elhabiri, Mourad; Krzyczmonik, Anna; Forsback, Sarita; Solin, Olof; et al.
Abstract: We report the synthesis and reactivity of 4‐fluorosydnones, a unique class of mesoionic dipoles displaying exquisite reactivity towards both copper‐catalyzed and strain‐promoted cycloaddition reactions with alkynes. Synthetic access to these new mesoionic compounds was granted by electrophilic fluorination of σ‐sydnone Pd II precursors in the presence of Selectfluor. Their reactions with terminal and cyclic alkynes were found to proceed very rapidly and selectively, affording 5‐fluoro‐1, 4‐pyrazoles with bimolecular rate constants up to 10 4  m −1  s −1, surpassing those documented in the literature with cycloalkynes. Kinetic studies were carried out to unravel the mechanism of the reaction, and the value of 4‐fluorosydnones was further highlighted by successful radiolabeling with [ 18 F]Selectfluor.